What are mechanisms in social science? (review) - Leuridan, Bert (Metascience, 2012)
Why should we introduce the notion of analytical sociology into the field of sociology, and why should it be linked to the concept of mechanism? With these two principal questions, Pierre Demeulenaere, Professor of Sociological Theory and Philosophy of the Social Sciences at the University of Paris-Sorbonne, opens his Analytical Sociology and Social Mechanisms, a collection of thirteen papers written by social scientists and philosophers of the social sciences (1). Not every contributor should be considered an analytical sociologist. Rather than being a manifesto either pro or contra analytical sociology and the use of mechanisms, it is an attempt to reflect upon the key issues involved in sociological explanation (3). Even though several chapters raise very interesting points, the overall impression one gets from this book is that analytical sociology fails to redeem its main promise, viz. to add clarity, precision, and conceptual rigor to sociology, especially regarding one of it